THE USE OF LASER AS THERAPY FOR ORAL PARESTHESIA : Penggunaan Laser sebagai Terapi untuk Parestesia Oral - Hendri Poernomo; Maya Sari Dewi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2021)
Introduction: Generally, paresthesia are a pain or uncomfortable sense or abnormality feeling like a burned, sweating, etc. The symptoms can be temporary or permanent, an acute nerve injury will reduce risk of permanent paresthesia. Review: Paresthesia can caused by local anesthesia ( injection method), extraction of third molar, dental implant, endodontic treatment, and trauma. It can prevented by proper patient identification, treatment planning and procedure. The management of paresthesia are observation, Physiologic treatment (cryotherapy, electro-iontophoresis, heat-therapy, massage treatment or acupunture), pharmacology therapy (antibiotics, anti- inflamation, antidepressant, neurotropic group, and topical), phsychologic therapy and laser therapy. Conclusion: Using Laser for paresthesia are to accelerate and enhanced regeneration the nerve tissue. With low-level laser it wiil be e xpected to healing an injured nerve.